2017
DOI: 10.1016/j.culher.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A complete methodology for the mechanical diagnosis of statue provided by innovative uses of 3D model. Application to the imperial marble statue of Alba-la-Romaine (France)

Abstract: International audienceA multidisciplinary methodology is presented to assess the mechanical behaviour of a marble statue with complex fracture plans and localized cracks. Firstly, a 3D model is generated by photogrammetry. Its underlying geometrical data provide valuable insight for the physical characterisation and the numerical analysis. Indeed, the ultrasound analysis, which is usually impossible on such a complex shape, is achieved thanks to the accurate measures of distance between transmitter and receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
6
0
1
Order By: Relevance
“…This method is very suitable in the field of mechanical engineering, but it is time consuming for complex and large buildings. Due to the complexity and irregularity typical of historic masonry buildings, the "Create mesh and solid model" approach is considered the most performing (Bagnéris et al, 2017). In this line, the Level of Detail (LOD) of mesh is an element of great importance to obtaining a reliable structural analysis (Spangher and Visintini, 2015) The objective of an ever-increasing LOD highlights two sides of the same coin: on one hand it improves the reliability and quality of the analysis and carried out evaluations (Giaccone et al, 2020), on the other it causes interoperability issues.…”
Section: Structural Model Generation Approachesmentioning
confidence: 99%
“…This method is very suitable in the field of mechanical engineering, but it is time consuming for complex and large buildings. Due to the complexity and irregularity typical of historic masonry buildings, the "Create mesh and solid model" approach is considered the most performing (Bagnéris et al, 2017). In this line, the Level of Detail (LOD) of mesh is an element of great importance to obtaining a reliable structural analysis (Spangher and Visintini, 2015) The objective of an ever-increasing LOD highlights two sides of the same coin: on one hand it improves the reliability and quality of the analysis and carried out evaluations (Giaccone et al, 2020), on the other it causes interoperability issues.…”
Section: Structural Model Generation Approachesmentioning
confidence: 99%
“…Virtual reality and computer graphics are considered by specialists in interpretative studies [1] and in-depth diagnostic analyses [2] as precious interaction tools to simulate the physical restoration of ancient sculptures in a non-invasive way [3].…”
Section: Introductionmentioning
confidence: 99%
“…Peculiar studies and design activities involve seismic preservation and monitoring, as demonstrated in [3]. Simulations for structural integrity are also increasing their role: besides the architectural field, original applications were carried out to evaluate stability of many statues such as the roman equestrian bronze of Marco Aurelio [4] or the imperial marble statue of Alba-la-Romaine (France) [5]. This work also demonstrates that many different CAD investigations may be provided starting from digital acquisition, such as measurement report and collection [6] and posture restoration.…”
Section: Introductionmentioning
confidence: 99%